Effects of silane functionalization on the properties of carbon nanotube/epoxy nanocomposites - Ma, P.C.; Kim, J.K.; Tang, B.Z.
The effects of silane functionalization of multi-wall carbon nanotubes (CNTs)on properties of CNT/epoxy nanocomposites are investigated in this work. Epoxy-based nanocomposites reinforced with CNTs with and without functionalization were prepared. The properties of nanocomposites were characterized extensively using the scanning electronic microscopy (SEM), electrical conductivity measurement, thermo-gravimetric analysis (TGA), dynamic mechanical analysis (DMA), three-point bending test and fracture toughness measurement. The results showed that grafting silane molecules onto the CNT surface improved the dispersion of CNTs in epoxy along with much enhanced mechanical and thermal properties as well as fracture resistance of nanocomposites compared to those containing CNTs without functionalization. The electrical conductivity of nanocomposites decreased due to the wrapping of CNTs with non-conductive silane molecules. These findings confirmed the improved interfacial interactions arising from covalent bonds between the functionalized CNTs and epoxy resin.
Keywords: A. POLYMER-MATRIX COMPOSITES (PMCS); B. ELECTRICAL PROPERTIES; B. THERMAL PROPERTIES; B. MECHANICAL PROPERTIES; CARBON NANOTUBES (CNTS)